(untitled) (Global Journal of Medical Research, 2017)
The global burden of non-communicable diseases (NCD’s) is escalating, principally due to a sharp rise in developing countries experiences of rapid economic transitions from subsistence and agricultural based economies to more technology based economies that are characteristic of sedentary based employment. Lifestyle changes in Mauritius too, with a population of barely 1.3 million inhabitants, have resulted in dramatic increases in the incidence of Type 11 diabetes. Diabetes mellitus is a condition in which the body’s capacity to utilise glucose, fat and protein is disturbed due to insulin deficiency or insulin resistance. The epidemic is chiefly type II diabetes which along with genetic susceptibility, particularly in certain ethnic groups such as Asians, is brought on by environmental and behavioural factors. Gestational Type 2 Diabetes (GDM) is defined as carbohydrate intolerance that begins or is first recognised during pregnancy. During pregnancy, the women is objectified, feeling a loss of control and an awareness of having an unwell, high risk body. Findings showed that pregnant women with GDM this study as extremely vulnerable. Behaviours of health professionals, such as nurses, midwives and physicians and of relatives, friends and employers influenced the women. An open caring relationship where the individual women is understood and supported, empowered to strive for normal glycaemia, and encouraged to be reconciled with her disease. It also includes informing her partner and other significant persons about her need for support.